Does Shari’ah supervisory board characteristics affect Islamic banks’ financial performance? Evidence from Saudi Arabia - Mohamed Sharif Bashir; Mahmoud Mohamed Ali Mahmoud Edris; Muslichah Muslichah (Virtus Interpress, 2024)
Corporate Board: Role, Duties and Composition Volume: 19 Issue: 2